2017
DOI: 10.1093/rheumatology/kex002
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of lymphocyte count transition in lymphoproliferative disorder in patients with rheumatoid arthritis treated with methotrexate

Abstract: A significant decrease in lymphocyte count at the LPD diagnosis and its restoration after MTX withdrawal were markedly associated with spontaneous regression of LPD developing during MTX treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 13 publications
7
28
0
Order By: Relevance
“…The ALCs of both patients were lower than 500/μl at the time of diagnosis and increased rapidly 2 weeks after MTX was discontinued. A similar relationship between ALC recovery and disease regression has been reported (15,16). MTX withdrawal resulted in immunological recovery and CR in 25-69% of patients with MTX-DLBCL (4,14,17).…”
Section: Discussionsupporting
confidence: 74%
“…The ALCs of both patients were lower than 500/μl at the time of diagnosis and increased rapidly 2 weeks after MTX was discontinued. A similar relationship between ALC recovery and disease regression has been reported (15,16). MTX withdrawal resulted in immunological recovery and CR in 25-69% of patients with MTX-DLBCL (4,14,17).…”
Section: Discussionsupporting
confidence: 74%
“…40 Our study also demonstrated that LPD in recent RA patients mostly developed under the condition of low disease activity, possibly due to the increase in MTX dose and the wide spread use of biologic agents. 41 It has been suggested that the balance of risk of LPD development related to RA inflammation and that due to RA treatment is changing. On the other hand, the disease activity score remained a significant risk factor for LPD in RA patients receiving MTX in another recent study.…”
Section: Ra Inflammation and Lpd Developmentmentioning
confidence: 99%
“…On the other hand, some MTX-LPD cases that are EBV negative and do not have increased serum EBV viral loads exhibit spontaneous regression after MTX cessation. 41 Among these MTX-LPD cases, the mechanism of spontaneous regression after MTX withdrawal is not well known. A study of EBV-negative PTLD with increased expression of BCL-6, decreased MUM-1 and IRF4, and less frequent nongerminal center compared with EBV-positive PTLD might be helpful to clarify the mechanism of EBV-negative MTX-LPD.…”
Section: Ebv-positive and -Negative Mtx-lpd In Ramentioning
confidence: 99%
“…Another study reported that spontaneous regression occurred in 18 of 20 cases following MTX cessation alone and that the rate of lymphocyte recovery 2 weeks after MTX cessation was higher in cases with regression than in those without regression (5). This observation was confirmed by a study showing that an increase in the lymphocyte count of >220 cells/μL at 2 weeks after MTX cessation may predict a favorable prognosis for spontaneous regression of LPD (25). Although EBER was negative in our case, the lymphocyte count rapidly recovered from 1,153 cells/μL to 2,655 cells/μL by 2 weeks after the cessation of MTX.…”
Section: Discussionmentioning
confidence: 84%